2007
DOI: 10.1158/0008-5472.can-06-3861
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Mutation of Apc Gene in Rat Colon Tumors and Mucin-Depleted Foci, Preneoplastic Lesions in Experimental Colon Carcinogenesis

Abstract: Mucin-depleted foci (MDF) are microscopic dysplastic lesions induced in the colon of rodents by specific colon carcinogens. Most MDF show Wnt pathway activation, whereas only a subset shows mutations in the Ctnnb1 gene, coding for B-catenin. Because Apc is a member of the Wnt pathway and the most frequent mutated gene in human colon cancer, we tested whether MDF harbor Apc mutations. F344 rats were treated twice with 150 mg/kg of 1,2-dimethylhydrazine. After 15 or 28 weeks, MDF, aberrant crypt foci (ACF), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 65 publications
(86 citation statements)
references
References 17 publications
(26 reference statements)
4
81
0
1
Order By: Relevance
“…Constitutive activation of Wnt-pathway has been reported by us in MDF, 3 and is caused, at least for a part of these lesions, by genetic mutations in Apc and b-catenin genes. 3,4 Also, it is relevant to note that Wnt activation may downregulate MUC2 expression in vitro and that both COX-2 and i-NOS have been reported as target genes upregulated by Wnt. [40][41][42] It has also been reported that prostaglandin E2 (PGE2), produced by COX-2, may activate Wnt-signalling acting by its cognate G-coupled receptor.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Constitutive activation of Wnt-pathway has been reported by us in MDF, 3 and is caused, at least for a part of these lesions, by genetic mutations in Apc and b-catenin genes. 3,4 Also, it is relevant to note that Wnt activation may downregulate MUC2 expression in vitro and that both COX-2 and i-NOS have been reported as target genes upregulated by Wnt. [40][41][42] It has also been reported that prostaglandin E2 (PGE2), produced by COX-2, may activate Wnt-signalling acting by its cognate G-coupled receptor.…”
Section: Discussionmentioning
confidence: 99%
“…4 Due to the low amount of RNA available we studied only the expression of i-NOS and we found (Fig. 3) that it was expressed in all the MDF analysed, with a strong expression in the large MDF formed by 200 crypts (MDF4 in the fifth lane of the gel).…”
Section: Rt-pcr Experiments To Evaluate I-nos Expression In Mdfmentioning
confidence: 98%
See 3 more Smart Citations